1985
DOI: 10.3168/jds.s0022-0302(85)80988-7
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Temperature Patterns of Early Lactating Cows with Milking Parlor Cooling,

Abstract: Ten cows in early stages of lactation (less than 100 days postpartum) were used to test the effect of sprinkler/fan cooling on vaginal temperature patterns. Cows were assigned to two groups matched according to milk production. The trial was divided into three periods: period 1, when one group was treated and the other group was not, period 2, when neither group was treated, and period 3, when treatment was switched from period 1 between groups. Treatment consisted of forced air misting in a premilking holding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…These patterns are likely due to cows in our study having access to shade after treatment: relative to no cooling resources, shade alone can reduce body temperature but is less effective than sprinklers (e.g., Kendall et al, 2007). Others have similarly found that body temperature remained lower than controls for 1.5 h (Brown-Brandl et al, 2010) or even 2 to 4 h after spraying stopped (Araki et al, 1985;Kendall et al, 2007). Before converging with the control, body temperature in our sprinkler treatments returned to baseline values.…”
Section: Body Temperature Beyond the End Of Treatmentmentioning
confidence: 48%
See 3 more Smart Citations
“…These patterns are likely due to cows in our study having access to shade after treatment: relative to no cooling resources, shade alone can reduce body temperature but is less effective than sprinklers (e.g., Kendall et al, 2007). Others have similarly found that body temperature remained lower than controls for 1.5 h (Brown-Brandl et al, 2010) or even 2 to 4 h after spraying stopped (Araki et al, 1985;Kendall et al, 2007). Before converging with the control, body temperature in our sprinkler treatments returned to baseline values.…”
Section: Body Temperature Beyond the End Of Treatmentmentioning
confidence: 48%
“…When we applied ≥1.3 L/min, wind extended the duration, similar to when sprinklers are combined with fans (as reviewed by Collier et al, 2006). Others have similarly found body temperature to reach a nadir between 30 and 60 min after spraying stopped (Araki et al, 1985;Flamenbaum et al, 1986;Kendall et al, 2007).…”
Section: Body Temperature Beyond the End Of Treatmentmentioning
confidence: 74%
See 2 more Smart Citations
“…Physiological responses to spray in milder weather also indicate attempts to conserve heat. When cows are sprayed in the morning (Araki et al, 1985) or on days with air temperature <23 • C (Kendall et al, 2007) body temperature temporarily increases afterward. Also, when the torso is sprayed, skin temperature on the extremities decreases, consistent with vasoconstriction (Chen et al, 2015).…”
Section: Preferencementioning
confidence: 99%